Biotransformation modulation and genotoxicity in white seabream upon exposure to paralytic shellfish toxins produced by Gymnodinium catenatum - Costa, Pedro Reis (2019)
Fish are recurrently exposed to paralytic shellfish toxins (PSTs) produced by Gymnodinium catenatum. Nevertheless, the knowledge regarding metabolism of PSTs and their toxic effects in fish is scarce. Consequently, the current study aims to investigate the role of phase I and II detoxification enzymes on PST metabolism in the liver of white seabream (Diplodus sargus), assessing ethoxyresorufin-O-deethylase (EROD) and glutathione S-transferase (GST) activities. Moreover, the genotoxic potential of PSTs was examined through the erythrocytic nuclear abnormality (ENA) assay. Fish were intracoelomically (IC) injected with a nominal dose (expressed as saxitoxin equivalents) of 1.60 μg STXeq kg⁻¹ semipurified from a G. catenatum cell culture with previously determined toxin profile. Fish were sacrificed 2 and 6 days after IC injection. PST levels determined in fish liver were 15.2 and 12.2 μg STXeq kg⁻¹, respectively, at 2 and 6 days after the injection. Though several PSTs were administered, only dcSTX was detected in the liver after 2 and 6 days. This was regarded as an evidence that most of the N-sulfocarbamoyl and decarbamoyl toxins were rapidly biotransformed in D. sargus liver and/or eliminated. This was corroborated by a hepatic GST activity induction at 2 days after injection. Hepatic EROD activity was unresponsive to PSTs, suggesting that these toxins enter phase II of biotransformation directly. The genotoxic potential of PSTs was also demonstrated; these toxins were able to induce cytogenetic damage, such as chromosome (or chromatid) breaks or loss and segregational anomalies, measured by the ENA assay. Overall, this study pointed out the ecological risk associated with the contamination of fish with PSTs generated by G. catenatum blooms, providing the necessary first data for a proper interpretation of biomonitoring programs aiming to assess the impact of phytoplankton blooms in fish.